Partisipasi Masyarakat Dalam Penataan Ruang Terbuka Hijau di Kota Serang - Teguh Aris Munandar; Febri Saefulloh (Epistemik: Indonesian Journal of Social and Political Science, 2024)
This research specifically examined the arrangement of Green Open Space (RTH) in Serang City, its main purpose was to maintain the balance of ecosystems in the urban environment, improve the quality of the environment in the city to be healthier and cleaner, and be able to realize the balance between the natural environment and the artificial environment. This research uses the George C. Edward III theory, which states that communication, resources, disposition, and bureaucratic structure influence the success of policy implementation. The research method was carried out to reveal the truth or conclusion about an object and can be used as a basis for theory formation. The method used in this research was qualitative research methods. According to Bogdan and Taylor (in Farida, 2014: 89), qualitative research methods are research procedures that produce descriptive data in the form of written or spoken words from people or observed behavior. Based on the results of research on the Implementation of Green Open Space (RTH) Arrangement Policy in Serang City, researchers conclude that the implementation of the Green Open Space Arrangement policy in Serang City has not progressed sufficiently well. Green Open Space in Serang City has not reached 30% of the target. Whereas, there are still several other obstacles experienced in carrying out the Green Open Space Arrangement Policy in Serang City, among others; socialization activities carried out by the Environmental Agency of Serang City have not run optimally but the DLH continues to strive for this socialization activity so that the community was able to participate in Green Open Space Arrangement in Serang City.